Kajian Etika Keagamaan Masjid Agung Kudus dalam Program CSR PT. Sukun Wartono Indonesia - Alfiyan Chasanul Muna; Masudi M (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the practice of accepting Corporate Social Responsibility (CSR) funds from PT. Sukun Wartono Indonesia by the Kudus Grand Mosque Foundation from an Islamic religious ethics perspective. PT. Sukun, as a company engaged in the cigarette industry, poses an ethical dilemma for religious institutions that accept its assistance. Using a descriptive qualitative approach, this study explores the views of mosque administrators on the CSR assistance and analyzes them through the framework of maqasid al-shariah and the principle of maslahah mursalah. The results indicate that although the funds originate from a controversial industry, mosque administrators assess that the social and religious benefits outweigh the potential harms. The acceptance of funds is based on considerations of the greater good of the community and the principle of social justice, provided that the purpose of the funds aligns with Islamic values. This study emphasizes the importance of contextual and flexible policies in the management of religious social funds. It also recommends that future research examine the perspectives of companies, particularly in their public relations strategies and efforts to build their image through religiously-based CSR initiatives.